The Problems of Learning a Foreign Language: Difficulties with Learning Vocabulary in Second Language Acquisition - Sattarova Soadat Narzullayevna; Maratova Fotima Jamshidovna (Zien Journals, 2021)
This paper describes the problems of acquiring foreign languages (English) and it recommends strategies that can minimize the students’ problems in learning the English
Keywords: Second-language readers; discrimination; understanding meaning; remembering